Disease-free plantains - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Developing plantains resistant to the fungal disease, black sigatoka, is progressing faster than expected. Several cultivars have been successfully crossed with the wild banana which is highly resistant to the disease to produce resistant hybrids....